(untitled) (Chemical Engineering Research Bulletin, 2017)
The main objective of this work is to develop film and study the thermal characteristics of polysaccharides films at various concentration of carrageenan in the mixture by calculating activation energy of polysaccharides films. There were four (4) film samples of two polysaccharides combination; arabic gum (AG) and carrageenan (C) with different formulations; sample A, sample B, sample C and sample D prepared. Sample A film is the control sample that contained only arabic gum and distilled water (DI) with 40% weight arabic gum per volume DI water (w/v%). Meanwhile for sample B and C were prepared with concentration 40 w/v% of Arabic gum and two differents of carrageenan concentrations; 1 w/v% and 10 w/v% respectively. Polyethylene glycol 400 (PEG 400) as a plasticiser was added into sample D film. The sample films were thermally characterized using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) under nitrogen atmosphere. The major thermal transitions as well as, activation energies of the major decomposition stages were determined. Sample A and B films exhibited the highest (112.43 kJ/mol) and the lowest (102.89 kJ/mol) activation energy of thermal decomposition, respectively. The activation energies were lower at larger amounts of sulfate groups from carrageenan on the degradation reactions. The DSC trend for all samples shows two (2) major intense peaks recorded in the DSC thermograms; an endothermic transition at temperature around 100°C and followed by an exothermic transition at temperature around 300°C. The endothermic transition is due to the heat absorption for dehydration of water, H2O and the decomposition of samples process. Meanwhile, the exothermic transition is caused by the formation of H2O, CO and CH4 in polysaccharide film from dehydration, depolymerisation and decomposition at the high-temperature stages. Chemical Engineering Research Bulletin 19(2017) 80-86